Influence of pH, Temperature and Metallic Behaviour of Ovis Lactoperoxidase - Joseph, P.V.; Jacob, Claramma; Haridas, M. (Asian Journal of Chemistry, 2010)
Circular dichroism (CD) spectra of sheep lactoperoxidase (sLP) were recorded in the wavelength region 190-250 run. The spectrum shows negative CD maximum at 207 and 216 run. It also shows that sLP maintains its structural integrity till 68°C and on further increase in temperature a sharp loss in CD spectrum was observed. Inductively coupled plasmaatomic emission spectroscopy (ICP-AES) and electron paramagnetic resonance (EPR) spectrum analysis revealed that sLP contains calcium, iron and also copper.